Uniform Vs Common Civil Code in India - Mohmood, Tahir (Journal of Dharma, 1986)
I have been a pilgrim in pursuit of legal knowledge, especiallv in the area of personal laws, for the past over two decades. During this period I written and spoken a lot on the issue of personal law reform and uniform civil code. The twenty-year record of the response of my fellow country-men to the views and opinions that I have humbly ventured on the subject has been rather chequered. In 1968 when I published my first book Changing Law of the Hindu Society, commenting orl the book in a prominent legal periodical of the time a leading legal luminary of the day generously borrowed poet Bhartendu's verse to say about me. "This Musalmara-Harijan deserves the sacrifice of lakhs of Hindus Eight Years later in 1976 when my anthological work, An Indian Civil Code and •the Islamic Law was published, writing the foreword to the book an eminent juristjudge of the country graciously found in me "a pioneering jurisprudent and a socialogist-cum-jurist with a bee in his bonnet." Another ten years have since passed and now certain critics have thought it fit to contemptuously confer on me appellations like "fundamentalist, obscurantist and somersaulter." Eighteen years ago this "MusalmanHarijan" deserved sacrifice of lakhs of Hindus for his forceful plea that certain aspects of the traditional Hindu Law be protected against the increasing onslaught of the. western legal culture. My 1976 book earned the prefatory panegyric from a great judge for my exposition of the potential of true Islamic law to become the major constituent of the future civil code of India. The labels of fundamentalism and obscurantism etc, now stuck on me by some so-called naticnalists are attributable to my assertion that a uniform civil code cannot.